Pengenalan Game Edukasi untuk Meningkatkan Perbendaharaan Kosa Kata Benda dalam Bahasa Inggris - Hariadi, Fajar; Jumalia, Jumalia; Talakua, Alfrian Carmen (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2023)
English is one of the subjects in the school curriculum in Indonesia. One of the English learning materials in class 3 of East Sumba 1 State Madrasah Ibtidaiyah (MIN) is the introduction to objects in English. The current learning process combined with educational game learning media shows an increase in the ability of 28 children to vocabulary nouns in English by 14.54% from the pre-test average result of 78 to 90 on the post-test results. The results of community service show that guidance and empowerment in learning English using educational games have a positive impact and get a good response from students. Empowerment has an important role in encouraging student motivation and increasing student achievement. It is hoped that this community service activity can be sustainable and become one of the collaborations between institutions so that these institutions help form an intelligent, wise and prosperous society.